Challenges of Society Era Education 5.0: Revitalization of Teacher Competencies and Learning Models - Eliwatis, Eliwatis; Aprison, Wedra; Maimori, Romi; Herawati, Susi; Putri, Yelli Masmida (Yayasan Minang Darussalam, 2022)
The rapid development of information technology has penetrated all aspects of human life, including education. The era of society 5.0 emerged as an anticipation of turmoil and disruption due to the industrial revolution 4.0. This change is clearly a challenge for the world of education, especially teachers as central figures in education because educational outputs are expected to have critical thinking skills, problem solving skills, communication and collaboration skills and innovation skills. For this reason, teachers must have competence in transforming learning from manual learning to digital but no longer just using technology but more as a driver (human centered) by controlling the use of technology in learning. Furthermore, this paper describes the challenges for the world of education in the era of society 5.0, what competencies must be possessed by teachers and what learning models must be used. The research method used is descriptive qualitative through library research, the data source is literature related to the discussion, the data collection method is literature study. Data analysis used content analysis method which is descriptive analysis. The results of the study show that teachers must have several main abilities including educational competence by being a role model for students, competence in research, competence for digital (digital literacy), global competence in globalization, competence leadership, competence communication and team working competence of critical thinking , competence creativity and problem solving. The learning model in the era of society 5.0 refers to three abilities, namely learning skills, literacy skills, and life skills.